Keratin-reinforced cellulose filaments from ionic liquid solutions. Issue 91 (16th September 2016) - Kammiovirta, Kari; Jääskeläinen, Anna-Stiina; Kuutti, Lauri; Holopainen-Mantila, Ulla; Paananen, Arja; Suurnäkki, Anna; Orelma, Hannes
Abstract : Cellulose-based filaments produced with ionic liquid-based processes have high application potential in textiles and composites to replace cotton fibres. Abstract : Cellulose-based filaments produced with ionic liquid-based processes have high application potential in textiles and composites to replace cotton fibres. These filaments already have unique properties that could be further improved with the addition of proteins. Keratin from poultry feathers is currently a low-value material that has potential as a renewable feedstock in material applications. In this study, cellulose filaments with chicken feather keratin were prepared by wet-spinning from an ionic liquid solution. Both keratin and cellulose were dissolved in [EMIM]AcO and spun into ethanol to regenerate cellulose and keratin and wash out the ionic liquid. The effect of keratin addition on the filament properties was investigated by microscopic, spectroscopic and strength analyses. It was observed that a small keratin addition into the cellulosic filaments improved the mechanical properties remarkably, whereas high keratin additions resulted in reduced mechanical performance. Keratin accumulation on the surface of the prepared filaments was observed. In addition, based on FTIR spectroscopy, it is likely that the morphology of cellulose changed from cellulose I to II and the β-sheets in feather keratin unfolded to unordered keratin upon dissolution and regeneration. The cellulose–protein filaments may find applications from areas where good biocompatibility and easy modifiability are required characteristics.